1997
DOI: 10.1074/jbc.272.41.25899
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Evidence for Multiple Ca2+-binding Domains in the Type 1 Inositol 1,4,5-Trisphosphate Receptor

Abstract: Structural and functional analyses were used to investigate the regulation of the inositol 1,4,5-trisphosphate (InsP 3 ) receptor (InsP 3 R) by Ca 2؉ . To define the structural determinants for Ca 2؉ binding, cDNAs encoding GST fusion proteins that covered the complete linear cytosolic sequence of the InsP 3 R-1 were expressed in bacteria. The fusion proteins were screened for Ca 2؉ and ruthenium red binding through the use of 45 The inositol 1,4,5-trisphosphate receptor (InsP 3 R) 1 is an intracellular Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 62 publications
4
107
0
Order By: Relevance
“…Stimulation of IP 3 R by cytosolic Ca 2þ is universally observed even with purified IP 3 R reconstituted into lipid bilayers (Ferris et al 1989;Hirota et al 1995;Michikawa et al 1999), suggesting that this essential Ca 2þ -binding site probably resides within the primary sequence of the IP 3 R. At least seven cytosolic Ca 2þ -binding sites have been identified within IP 3 R1 (Sienaert et al 1996;Sienaert et al 1997), but the physiological relevance of these sites is unresolved. Two of the sites (residues 304-381 and 378-450) are within the IP 3 -binding core, for which there is a high-resolution structure (Bosanac et al 2002).…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of IP 3 R by cytosolic Ca 2þ is universally observed even with purified IP 3 R reconstituted into lipid bilayers (Ferris et al 1989;Hirota et al 1995;Michikawa et al 1999), suggesting that this essential Ca 2þ -binding site probably resides within the primary sequence of the IP 3 R. At least seven cytosolic Ca 2þ -binding sites have been identified within IP 3 R1 (Sienaert et al 1996;Sienaert et al 1997), but the physiological relevance of these sites is unresolved. Two of the sites (residues 304-381 and 378-450) are within the IP 3 -binding core, for which there is a high-resolution structure (Bosanac et al 2002).…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
“…However, point mutations of several of these acidic residues had no effect on Ca 2þ -regulation of IP 3 R (Joseph et al 2005). The remaining Ca 2þ -binding sites fall within the central region of the IP 3 R (Sienaert et al 1996;Sienaert et al 1997). The site between residues 1347 -1426 is interesting because its proximity to a calmodulin (CaM)-binding region is reminiscent of RyR, which have two CaM-binding regions within 200 residues of high-affinity Ca 2þ -binding sites, and a third flanked by two high-affinity Ca 2þ -binding sites (Chen and MacLennan 1994).…”
Section: Regulation Of Ip 3 Receptors By Ca 2þ and Ipmentioning
confidence: 99%
“…We have found that the Ca# + -dependent inhibition of InsP $ binding to cerebellar microsomes might result from a direct interaction of Ca# + with InsP $ R1 [29]. Two of the Ca# + -binding regions identified in the cytoplasmic part of InsP $ R1 are located in the InsP $ -binding domain [25], making these sites reasonable candidates for the mediation of the competitive inhibitory effects of Ca# + described here. Recently, biphasic dependence on Ca# + of InsP $ R channel activity was found to occur with cerebellar receptor isolated and reconstituted in lipid bilayers, suggesting direct effects of Ca# + on this protein [44].…”
Section: [$H]inspmentioning
confidence: 67%
“…However, distinct and noninteracting inhibitory sites might also make a significant contribution to the high degree of sigmoidicity of these curves [40]. Several Ca# + -binding sites have been identified in the InsP $ R1 subunit [25].…”
Section: [$H]inspmentioning
confidence: 99%
See 1 more Smart Citation